Comparison (Constitution, Government System, and Enforcement of Human Rights) United State of America with United Kingdom - Nurul Fadhilah (Journal of Law and Administrative Science, 2024)
Abstract. The United States has a written constitutional system in the form of a republic with clear boundaries of power between the executive, legislative, and judicial branches. In contrast, the United Kingdom has an unwritten constitution based on various sources, such as statutes, conventions, and court decisions, with a constitutional monarchy and parliament playing key roles. Second, the state upholds civil rights and individual freedoms, and has an impact on the political and legal systems for the implementation of human rights. Through a comparative approach, this article provides further understanding of the differences and similarities between the constitutions and systems of government of the two countries in upholding the principles of democracy and human rights, and the consequences of these differences on national and international politics.